Computers in the Legislature - Frank B. Ryan (Washington University Law Quarterly, 1977)
This Article focuses on the impact of the computer on the legislative process. Dr. Ryan identifies two major problems with computer use which may prevent it from becoming the control mechanism envisioned by Professor Dorsey. First, although the House of Representatives is currently using a computer for various administrative, legislative, and information gathering functions, its potential is limited by the lack of imagination of its users. Thus, a fully automated administrative system is impossible in the House of Representatives because of the narrow perspective of numerous members, each guarding his or her own power base. In addition, although it is possible to install computer terminals in each member's office to receive relevant legislative information with which he or she might intelligently govern, who will decide what information will flow through the centralized computer information system? Who will define “relevant” and how will the system continually be updated? The computer provides the means to control and direct technological and social change; however, its potential can be exploited only if we are capable of controlling it. The experience of the House of Representatives suggests that we have far to go.
Keywords: Computing and the Law